Australian laterites reveal mechanisms governing scandium dynamics in the critical zone. (1st September 2019) - Chassé, Mathieu; Griffin, William L.; O'Reilly, Suzanne Y.; Calas, Georges
Abstract: Scandium is often considered as immobile during chemical weathering, based on its low solubility. In contrast to other conservative ( i.e. relatively immobile) elements incorporated into accessory minerals resistant to weathering ( e.g. zirconium, thorium or niobium), the scarcity of scandium minerals indicates that the processes accounting for scandium's immobilisation are distinctive. However, the evolution of scandium speciation during weathering is unknown, limiting the understanding of the processes controlling its dynamics in the critical zone. Exceptional scandium concentrations in east Australian laterites provide the possibility of unravelling these mechanisms. We follow scandium speciation through thick lateritic profiles ( > 30 m) using a multiscale mineralogical and spectroscopic approach involving electron microprobe, laser-ablation–inductively coupled plasma mass spectrometry, selective leaching and X-ray absorption near-edge structure spectroscopy, complemented by mass-transfer calculations. We show that the initial reservoir of scandium contained in the parent rock is preserved under reducing conditions occurring in the lowest horizons of the profiles. The dissolution of scandium-bearing clinopyroxene generates smectitic clays that immobilise and concentrate scandium. It is subsequently trapped in the lateritic duricrust by goethite. Scandium mobilisation appears in this horizon and increases upward as a result of the dissolution of goethite, possibly assisted by dissolved organic matter, and the precipitation of hematite. Molecular-scale analyses demonstrate that changes in speciation govern scandium dynamics, with substitution in smectitic clays and adsorption on iron oxyhydroxides playing a crucial role in scandium immobility in the saprolite and lower lateritic duricrust. The higher affinity of scandium for goethite relative to hematite drives scandium mobilisation in the upper lateritic duricrust, leading to its concentration downward in the lower lateritic duricrust. These successive mechanisms illustrate how the unique complexity of the critical zone leads to scandium concentrations that may form new types of world-class scandium deposits. Comparison with conservative elements and with rare-earth elements, expected to have similar geochemical properties, emphasizes the unique behaviour of scandium in the critical zone. While scandium remains immobile during the early stages of weathering, intense and long-term alteration processes, observed in lateritic contexts, lead to scandium mobilisation. This study highlights the dependence of scandium mobility on weathering conditions.